Synovial Inflammation in Patients with Hallux Valgus is Similar to Changes Seen in Those with Hallux Rigidus - Anthony L. Karzon; Rishin J. Kadakia MD; Michelle M. Coleman MD, PhD; Sameh (Sam) A. Labib MD; Joseph E. Jacobson MD; Jason T. Bariteau MD (Foot & Ankle Orthopaedics, 2022)
Category: Basic Sciences/Biologics; Bunion Introduction/Purpose: Hallux valgus and hallux rigidus are common disorders that can have functional limitations for patients. Although both involve pathology centered around the first metatarsophalangeal joint (MTPJ), the surgical management for both greatly varies. Inflammatory changes in a joint play a critical role in the development of pain and dysfunction. It has been postulated previously that patients with bunion deformity can develop arthritic changes in the long-term. The purpose of this work is to study and compare the synovial tissue inflammation in patients with hallux valgus and hallux rigidus. Methods: A prospective study of patients aged 25 to 75 years undergoing either surgical management of hallux valgus or hallux rigidus between January 2021 and December 2021 was conducted following IRB approval. Tissue samples from the synovium were collected at the time of procedure and sent for processing and histology. The samples were graded in a blinded fashion based on the degree of inflammation. Morphological features of the synovectomy specimens undergoing histopathologic analysis were scored by synovial lining cell layer hyperplasia, the extent of inflammatory synovium infiltration, as well as pannus formation via activation of synovial stroma and resident cells. All parameters were graded from 0 (absent), 1 (slight), 2 (moderate), to 3 (strong). Statistical analysis was conducted to compare the level of inflammation between patients who had hallux valgus and those that had hallux rigidus. Results: A total of twenty-one samples were collected. One sample was excluded as there was inadequate tissue for analysis. There were eight patients with hallux rigidus and twelve patients with hallux valgus. Mean age at the time of sample collection was 59.3 years (SD=11.9). There was no significant difference in the synovium inflammatory scores (M=5.0, SD=2.25) between the two groups, t(18)= 1.704, p=.106, ([CI .95]: -0.388, 3.722). Moreover, Cohen's effect size value (d=0.78) suggests medium to high practical significance. Conclusion: Understanding the intra-articular impact of hallux valgus is important when considering treatment options. The amount of inflammation in the synovial tissue of hallux valgus patients in this study was similar to that of patients with hallux rigidus suggesting that there is intra-articular inflammation in patients with hallux valgus. Further work will need to be performed to determine if this increased inflammation influences outcomes or has an effect on treatment.